Micro-Mechanical Bending (M2 B) method for Carbon Nanotube (CNT) based sensor fabrication - Mohd Razib, M. A.; Saleh, Tanveer; Hassan, M. A. (2014)

(untitled)
Vertically aligned carbon nanotubes (VACNTs forest) array is known to be the darkest material on earth. However, post processing of VACNTs array by micro mechanical bending (M2B) causes the individual CNT to be bent, flattened and reflective. This interesting change in the optical property of CNT forest opens the gateway, to use it as displacement sensor both for linear and angular motion. This paper investigates experimentally how different parameters of M2B process affect the morphology of the patterned zone which is very important in fabricating this type of sensor. Micro-mechanical bending is locally applied to the targeted area in order to change the physical property of carbon nanotube. The factors that govern the resultant have been first identified; rotation spindle rate, bending speed rate, step size and total depth of bend. The resultant has been analyzed using Field Emission Scanning Electron Microscopy (FE-SEM) technique to observe the differences in surface roughness and structural integrity, revealing their dependence on the machining parameters.